ANALISIS DAMPAK PENERAPAN TEKNOLOGI ARTIFICIAL INTELLIGENCE TERHADAP EFEKTIFITAS PEMBELAJARAN BAGI SISWA SMK - Machfud, Syaeful; Halawa, Hedwin Winata; Gea, Kurniaman; Rizky, Mochammad; Indriani, Rifdah (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to analyse the application of Artificial Intelligence (AI) technology to the effectiveness of student learning at SMK Nusantara 1 Ciputat. Using a descriptive qualitative research design, the research subjects involved 30 students selected through purposive sampling. Data were collected through semi-structured interviews and observations, then analysed using thematic analysis method with data triangulation. The results showed that the application of AI technology was able to improve students' understanding of the basic concepts of AI, its types, and its practical applications. After the training, 80% of students understood the basic concepts of AI, an increase from 20% before the training. However, the main challenges faced include infrastructure limitations, such as internet connection, as well as the need for further training for teachers. Support from the school and improved infrastructure are important factors for more effective AI implementation. This research contributes to the vocational education literature in Indonesia by demonstrating the potential of AI as an interactive and adaptive learning tool, and providing recommendations to overcome implementation challenges. Further studies with a broader scope are recommended to explore the long-term impact of AI in vocational learning.